(untitled) (The Shivapuri Journal, 2025)
National unity is vital for a nation’s strength and stability, with strategic significance across social, political, and economic domains. A thorough understanding of national unity is essential for promoting peace, security, and prosperity, while strengthening social cohesion and preserving national identity. There are numerous factors that either contribute or influence the realm of national unity while enabling policymakers to leverage it effectively. The complexity of maintaining national unity hugely demands intentional efforts to promote inclusivity, equity and people’s mindset to work together for the common good. A country should formulate policies that foster a shared identity and ensure equal opportunities for all if it aims to create a more promising and prosperous future for its citizens. Therefore, the strategic imperative of national unity remains not just as a desirable goal but a crucial necessity for the social, political, and economic stability of any nation.